Exploring the Dual Role of Quizzes in Shaping Students’ Learning Habits, Autonomy, and Assessment Dependency - Sry Wahyuni; Isnaeni (Science Tech Group, 2026)
This study explores the role of quizzes in shaping students’ learning behavior, with a particular focus on learning habits, autonomy, and assessment dependency in higher education. While quizzes are widely recognized as effective formative assessment tools, their influence on students’ learning processes remains underexplored. This study contributes to the achievement of Sustainable Development Goal (SDG) 4, particularly SDG 4.4, SDG 4.7, and SDG 4.a, by promoting autonomous and supportive learning environments. It employed a qualitative research design using semi-structured interviews with 38 students at Universitas Negeri Makassar who experienced regular quiz implementation in their courses. The data were analyzed using thematic analysis to identify patterns in students’ perceptions and behaviors. The findings reveal that quizzes shape students’ learning behavior in four interconnected ways. First, quizzes promote structured learning habits by encouraging students to study in a time-bound and assessment-oriented manner. Second, quizzes foster assessment dependency, where students’ engagement is strongly tied to the presence of evaluation. Third, a tension emerges between external control and learning autonomy, as students feel compelled to study due to quizzes rather than personal motivation. Finally, quizzes contribute to academic pressure and cognitive load, particularly when combined with other academic demands. Overall, this study highlights the dual role of quizzes as both supportive and controlling learning tools. While they can enhance engagement and discipline, over-reliance on quizzes may limit the development of autonomous and self-regulated learning. Therefore, assessment practices should adopt a more balanced and autonomy-supportive approach to promote sustainable learning in higher education.